HOST-SPECIFICITY AND BIOASSAY OF TOXIN FROM RHIZOCTONIA SOLANI KUHN CAUSING SHEATH BLIGHT DISEASE OF RICE - Pascual, Maria Lima; Mirnia, Eka; Langres, Joanne (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Sheath blight is one of the major diseases of rice worldwide which is caused by Rhizoctonia solani and known to produce phytotoxin. In this study, the pathogenic ability of pure culture isolate was assessed in standing susceptible check rice plants and host specificity  R. solani toxin was evaluated through detached leaf bioassay. The effect of high temperature (by boiling) and different concentrations to toxin activity were also assessed through seed germination and seedling growth of susceptible (TN1 variety) and moderately resistant (IR72) rice varieties. Extracted toxin from the pure culture of R. solani isolate from Los Baños, Laguna, Philippines induced sheath blight disease in rice but not in corn (IPBVar2) and tomato (Red Cherry) which implied host specificity of the toxin. Percent germination and seedling growth of susceptible (TN1) and moderately resistant (IR72) rice varieties were significantly affected when applied with crude and/or boiled toxin indicating stability of RS toxin at high temperature. Low concentration of the RS toxin, however, reduced its infectivity in both rice varieties and was comparable with the control in terms of percent germination and seedling growth. Findings of the present study further confirmed (1) the pathogenic activity of RS toxin to rice (TN1 variety) but not pathogenic to tomato (Red Cherry) and corn (IPBVar2), (2) the high temperature did not affect  R. solani toxin pathogenic activity while (3) level of concentration of the R. solani toxin affects its effectiveness on the diseases.